Low-Dose Radiation Therapy for Severe COVID-19 Pneumonia: A Randomized Double-Blind Study - Papachristofilou, Alexandros (Int J Radiat Oncol Biol Phys, 2021)
PURPOSE: The morbidity and mortality of patients requiring mechanical ventilation for coronavirus disease 2019 (COVID-19) pneumonia is considerable. We studied the use of whole-lung low-dose radiation therapy (LDRT) in this patient cohort. METHODS AND MATERIALS: Patients admitted to the intensive care unit and requiring mechanical ventilation for COVID-19 pneumonia were included in this randomized double-blind study. Patients were randomized to 1 Gy whole-lung LDRT or sham irradiation (sham-RT). Treatment group allocation was concealed from patients and intensive care unit clinicians, who treated patients according to the current standard of care. Patients were followed for the primary endpoint of ventilator-free days at day 15 postintervention. Secondary endpoints included overall survival, as well as changes in oxygenation and inflammatory markers. RESULTS: Twenty-two patients were randomized to either whole-lung LDRT or sham-RT between November and December 2020. Patients were generally elderly and comorbid, with a median age of 75 years in both arms. No difference in 15-day ventilator-free days was observed between groups (P = 1.00), with a median of 0 days (range, 0-9) in the LDRT arm and 0 days (range, 0-13) in the sham-RT arm. Overall survival at 28 days was identical at 63.6% (95% confidence interval, 40.7%-99.5%) in both arms (P = .69). Apart from a more pronounced reduction in lymphocyte counts after LDRT (P < .01), analyses of secondary endpoints revealed no significant differences between the groups. CONCLUSIONS: Whole-lung LDRT failed to improve clinical outcomes in critically ill patients requiring mechanical ventilation for COVID-19 pneumonia.